Paws for Intervention: Perceptions About the Use of Dogs in Schools. Issue 1 (2nd January 2017) - Zents, Courtney E.; Fisk, Amy K.; Lauback, Cris W.
ABSTRACT: Research in the field of animal-assisted therapy has shown that therapy dogs have a positive social-emotional impact on individuals in hospitals, nursing homes, and counseling. Recently, the literature has suggested that therapy dogs can yield positive psychological, social, and academic outcomes in schools, although this research is quite limited. The intent of this study was to examine perceptions on the effectiveness of therapy dogs in schools for promoting students' psychological well-being, and an overall positive school climate. Preliminary evidence shows faculty and students from four rural school districts across Western New York indicated support for this emerging and viable school intervention. This qualitative and quantitative insight can help guide future research.